PENGARUH BEBAN PAJAK TANGGUHAN, LEVERAGE TERHADAP MANAJEMEN LABA MELALUI MANIPULASI RIIL(STUDI EMPIRIS PERUSAHAAN MANUFAKTUR 2010-2016) - RAHMANTO, KRESNANDA (Jurnal Akuntansi AKUNESA, 2017)
Abstract This study aims to provide empirical evidence of the effect of deferred tax expense and leverage to earnings management through manipulation of real activity in the manufacturing companies listed in Indonesia Stock Exchange in 2010-2016. The sample in this study are 127 manufacturing companies listed on Indonesia Stock Exchange (IDX) during 2010-2016 period. The method of analysis used is descriptive statistics, hypothesis test using multiple regression analysis. The results of this study prove that variable deferred tax expense and leverage simultaneously have an effect on earnings management through real activities manipulation. However partially deferred tax expense is not affected and leverage has negative effect. Keywords: Deferred Tax Expense, Leverage, Earnings Management, RealActivity.